profile
Опубликовано - 2 месяца назад | По предмету Математика | автор Аноним

Упростите выражения: 1) (x+2)(x-5)-3x(1-2x) 2) (a+3)(a-2)+(a-3)(a+6) 3) (x-7)(3x-2)-(5x+1)(2x-4) 4) (5x-2y)(3x+5y)-(2,5x-3y)(4x+8y)

  1. Ответ
    Ответ дан Орехов Никита

     1) (x + 2) * (x - 5) - 3 * x * (1 - 2 * x) = x- 5 * x + 2 * x - 10 - 3 * x + 6 * x= 7 * x- 6 * x - 10;

    n

    2) (a + 3) * (a - 2) + (a - 3) * (a + 6) = a2 - 2 * a + 3 * a - 6 + a+ 6 * a - 3 * a - 18 =
    2 * a+ 4 * a - 24 = a+ 2 * a - 12;

    n

    3) (x - 7) * (3 * x - 2) - (5 * x + 1) * (2 * x - 4) = 3 * x2  - 2 * x - 21 * x + 14 - (10 * x- 20 * x + 2 * x - 4) = 3 * x- 23 * x + 14 - 10 * x2  + 18 * x - 4 = -7 * x- 5 * x + 10;

    n

    4) (5 * x - 2 * y) * (3 * x + 5 * y) - (2,5 * x - 3 * y) * (4 * x + 8 * y) = 15 * x+ 25 * x * y - 6 * x * y - 10 * y- (10 * x+ 20 * x * y - 12 * x * y - 24 * y2) = 15 * x+ 19 * x * y - 10 * y- 10 * x- 8 * x * y + 24 * y=  5 * x+ 14 * y+ 11 * x * y;

    n

    5) (3 * a² + 5 * y) * (2 * a³ + y) - 7 * a³ * (a² - 3 * y) = 6 * a5 + 3 * a2 * y + 10 * a3 * y + 5 * y- 7 * a+ 21 * a3 * y= -a+ 3 * a2 * y + 31 * a3 * y + 5 * y.

    0



Топ пользователи